Risk factors for nosocomial bloodstream infection caused by multidrug resistant gram-negative bacilli in pediatrics - Mariana V. Arnoni (Brazilian Journal of Infectious Diseases)
The aim of this study was to identify the risk factors for nosocomial bloodstream infections by multidrug resistant Gram-negative bacilli. From November 2001 to December 2003, in the Pediatric Department of the Santa Casa de São Paulo, a retrospective case-control study was developed concerning patients who had nosocomial bloodstream infection caused by Gram-negative bacilli. Patients with multidrug resistant infections were designated as case patients, and control patients were those with an infection that did not meet the criteria for multidrug resistance. Previous use of central venous catheter and previous use of vancomycin plus third generation cephalosporins were associated to a higher chance of infections by multidrug resistant Gram-negative bacilli (Odds ratio - 5.8 and 5.2, respectively). Regarding sensitivity of the isolated agents, 47.8% were multidrug resistant, 54.2% were Klebsiella spp. ESBL producers and 36.4% were imipenem resistant Pseudomonas aeruginosa. The lethality rate was 36.9% in the studied cases and this rate was significantly higher in the group of patients with multidrug resistant infections (p=0.013). Risk factor identification as well as the knowledge of the susceptibility of the nosocomial infectious agents gave us the possibility to perform preventive and control strategies to reduce the costs and mortality related to these infections.